Composites Produced from Natural Rubber and Chrome-Tanned Leather Wastes: Evaluation of their In Vitro Toxicological Effects for Application in Footwear and Textile Industries - Cavalcante, Dalita G. S. M. [UNESP]; Gomes, Andressa S. [UNESP]; Santos, Renivaldo J. [UNESP]; Kerche-Silva, Leandra Ernst [UNESP]; Danna, Caroline Silva [UNESP]; Yoshihara, Eidi; Job, Aldo E. [UNESP] (Springer Nature, 2018)
A new composite has been developed from natural rubber and chrome-tanned leather waste for use in footwear and textile industries. The contribution of this material to environmental quality and sustained development should be highligh because chrome tanned leather wastes, a major environmental problem, can be recycled. However, the safety of this new material for human use is questionable, as it is already well reported in the literature that chromium, particularly in its hexavalent oxidation state, can be genotoxic and carcinogenic to living beings. Thus, the aim of this study was to evaluate in vitro biocompatibility of this composite material for possible use in the footwear and textile industries, through cytotoxicity, cell adhesion, and genotoxicity tests. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to measure both concentrations of total and hexavalent chromium. Based on the findings, it was concluded that the composite exhibits low levels of cytotoxicity and genotoxicity, and possesses favorable properties for initial cell adhesion. Furthermore, it was verified that the composites released low concentrations of chromium and that the predominant species released would be trivalent chromium. The results of the present study open the possibility of the incorporation of solid residues of tanned leather into chromium without necessarily the chromium contained in these residues influences the toxicity and genotoxicity of this new material.
Keywords: Cell line; Chromium; Cytotoxicity; Genotoxicity; Leather; Natural rubber